An interdisciplinary approach to improve surgical antimicrobial prophylaxis. Issue 2 (12th March 2018) - Conaty, Oisín; Gaughan, Leah; Downey, Colum; Carolan, Noreen; Brophy, Megan Joanne; Kavanagh, Ruth; McNamara, Deborah A.A.; Smyth, Edmond; Burns, Karen; Fitzpatrick, Fidelma
Abstract : Purpose: The purpose of this paper is to improve surgical antimicrobial prophylaxis (SAP) prescribing in orthopaedic surgery using the model for improvement framework. Design/methodology/approach: Orthopaedic patients receiving joint replacements, hip fracture repairs or open-reduction internal-fixation procedures were included. Antimicrobial(s); dose, time of administration and duration of SAP were evaluated for appropriateness based on the local SAP guidelines. After baseline data collection, a driver diagram was constructed with interventions devised for plan-do-study-act cycles. Data were fed back weekly using a point prevalence design (PPD). Interventions included SAP guideline changes, reminders and tools to support key messages. Findings: SAP in 168 orthopaedic surgeries from 15 June 2016 to 31 January 2017 was studied. Prescribing appropriateness improved from 20 to 78 per cent. Junior doctor changeover necessitated additional education and reminders. Practical implications: Due to constant staff changeover; continuous data collection, communication, education and reminders are essential to ensure continuous compliance with clinical guidance. Patients with hip fractures are difficult to weigh, requiring weight estimation for weight-based antimicrobial dosing. Unintended consequences of interventions included the necessity to change pre-operative workflow to accommodate reconstitution time of additional antimicrobials and inadvertent continuation of new antimicrobials post-operatively. Originality/value: Rather than perform the traditional retrospective focused audit, we established a prospective, continuous, interventional quality improvement (QI) project focusing on internal processes within the control of the project team with rapid cyclical changes and interventions. The weekly PPD was pragmatic and enabled the QI project to be sustained with no additional resources.